TI_GERICHTE 35.2023.71 vom 2. Oktober 2023 , STF di rinvio (8C_293/2023). Nessuna deduzione sociale: confermato. Decisione su opposizione confermata - TI Tribunale d'appello (2023)
STF di rinvio (8C_293/2023). Nessuna deduzione sociale: confermato. Decisione su opposizione confermata